The Antifungal Effect of Kesum Leaf (Polygonum minus Huds) in Ethanol Extract on Microsporum gypseum - Liauw, Josephine Johan; Rizki, Syarifah Nurulyanti; Natalia, Diana; Mahyarudin, Mahyarudin (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2021)
Introduction: Dermatophytosis or tinea is a disease found in the keratinized tissues caused by dermatophytes. The prolonged use of antifungal drugs has adverse effects on humans. Kesum leaves (Polygonum minus Huds) contains the secondary metabolite properties which can act as anti-fungi. Objective: This study aimed to determine the antifungal activity of ethanol extract of kesum leaves in inhibiting the Microsporum gypseum.Methods: Phytochemical analysis was performed using a test tube method and thin layer chromatography. The antifungal activity test used a disc diffusion method with the extract concentrations of 5%, 10%, 20%, 40%, and 80%. Kesum leaves macerated using ethanol 96% solvent. Itraconazole 8Âµl/disk and DMSO4 were respectively used as positive and negative control. Results: Phytochemical analysis on the ethanol extract of kesum leaves showed the secondary metabolite groups of flavonoids, alkaloids, terpenoids, phenolics, and saponins. Ethanol extract of kesum leaves did not form an inhibitory zone on the growth of Microsporum gypseum. Meanwhile in the positive control, in the form of itraconazole 8 Âµl/disk, the inhibition zone was formed around the disc with a mean value of 37.5 mm.Conclusion: Ethanol extract of kesum leaves (Polygonum minus Huds) has no antifungal activity against the growth of Microsporum gypseum.